1999
DOI: 10.1101/gad.13.4.412
|View full text |Cite
|
Sign up to set email alerts
|

Ski is a component of the histone deacetylase complex required for transcriptional repression by Mad and thyroid hormone receptor

Abstract: N-CoR (nuclear hormone receptor corepressor) was identified originally as a corepressor that binds to, and mediates transcriptional repression by, nuclear hormone receptors (Hö rlein et al. 1995). Thyroid-hormone and retinoic-acid receptors (TR and RAR) of the nuclear hormone receptor family actively repress the transcription of target genes in the absence of ligand (Chambon 1994;Mangelsdorf et al. 1995). Transcriptional repression is mediated by a conserved region in the aminoterminal part of the ligand-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
241
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(250 citation statements)
references
References 55 publications
4
241
3
Order By: Relevance
“…SnoN is a transcriptional co-repressor that interacts with Smad2/3 and Smad4, and represses TGF-β signalling through recruitment of HDAC (histone deacetylase) to Smads [40][41][42]. Bonni et al [21] have reported that Smurf2 associates with SnoN via Smad2, and induces ubiquitin-mediated degradation of SnoN, but not that of Smad2.…”
Section: Discussionmentioning
confidence: 99%
“…SnoN is a transcriptional co-repressor that interacts with Smad2/3 and Smad4, and represses TGF-β signalling through recruitment of HDAC (histone deacetylase) to Smads [40][41][42]. Bonni et al [21] have reported that Smurf2 associates with SnoN via Smad2, and induces ubiquitin-mediated degradation of SnoN, but not that of Smad2.…”
Section: Discussionmentioning
confidence: 99%
“…Ski has been shown to be involved in certain distinct signaling pathways including nuclear receptors (Dahl et al, 1998;Nomura et al, 1999;Ueki and Hayman, 2003b;Ritter et al, 2006), transforming growth factor-b (TGF-b) (Akiyoshi et al, 1999;Luo et al, 1999;Sun et al, 1999;Xu et al, 2000;Ueki and Hayman, 2003a) and tumor suppressors Tokitou et al, 1999;Khan et al, 2001) where Ski can act as a transcriptional corepressor. This is in part due to its direct and indirect interactions with histone deacetylase (HDAC) complexes including nuclear receptor-corepressor/silencing mediator for retinoid and thyroid hormone receptors (N-CoR/SMRT) and Sin3A corepressors Jepsen and Rosenfeld, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…SKI is dependent on interactions with other cellular partners, such as SMAD proteins, and transcriptional co-regulators including N-CoR, mSin3A, and histone deacetylases. 14,16 Remarkably, all SKI mutations described so far cluster into two domains: the R-SMAD binding domain, involved in TGFb signaling, and the DHD domain, which mediates binding to SNW1 and N-Cor proteins. The latter are essential for the transforming activity of SKI and for the recruitment of transcriptional corepressors.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Additionally, the SKI protein can recruit transcriptional corepressors including SNW1, N-CoR, and mSIN3 and forms a complex with histone deacetylases. 16,17 In vivo studies in Xenopus embryos, zebrafish, and mice have shown that SKI has a critical role in the development of neuronal and muscle cells or tissues. [18][19][20] Homozygous Ski-targeted mice show a major reduction in skeletal muscle mass and defects in cranial neural tube closure, manifestations that resemble those observed in SGS patients.…”
Section: Introductionmentioning
confidence: 99%